Technical-economic evaluation of the implementation of an integrated ethanol biorefinery: literature review - Pansiere Zavarise, Julio; de Araujo Vicente, Maristela; de Assis Ressel Pereira, Fabio; Pinotti, Laura Marina (Latin American Journal of Energy Research, 2025)
In Brazil, ethanol is a fuel produced in sugarcane biorefineries that generate sugar, ethanol and bioelectricity. The full use of the residual lignocellulosic biomass generated in these facilities can contribute to increasing ethanol production, although the relatively high costs of installing and operating second-generation ethanol production lines are still an obstacle. Thus, the objective of the present work was to perform a bibliographic review of publications on the simulation of integrated ethanol production processes in sugarcane biorefinery. To perform a bibliometrics of relevant publications on this topic, two scientific databases were consulted and the publications were selected by the date of publication, by the average number of annual citations and by the analysis of the expanded abstracts. The metadata of the selected publications were used for the scientific mapping carried out in the Bibliometrix software. Regarding the results of the bibliometric analysis, 152 publications were found and an annual growth rate of publications equal to 12.6% was observed. Most of the most productive authors in this research section are Brazilian and are associated with Brazilian universities and research institutions. From the literature review carried out, it was concluded that most of the feasibility analysis of sugarcane ethanol biorefinery projects are carried out in the Aspen Plus process simulator, combined with the use of electronic spreadsheets. In the selected studies, there is a consensus that the integrated production of ethanol presents higher productivity when compared to the autonomous operation of first-generation ethanol, although the technical difficulties of the production of second-generation ethanol still reside in the pre-treatment and enzymatic hydrolysis stages. As the main methodologies for the economic evaluation of ethanol biorefinery installation projects, the internal rate of return (IRR) and the evaluation of the cost of capital associated with the ethanol sale price stand out.
Keywords: Simulation; Bibliometrics; biomass